HTML & XHTML template master CD
Create web pages and learn to use HTML 4.01 and XHTML with on-screen tutorials, templates and hundreds of "cut and paste" clip-art items. This completely revised, award-winning product covers everything you need to create effective web pages, design fill-out forms, add digital images, use clip art, or master HTML/XHTML coding techniques.